Características socio económicas de los internos del centro de rehabilitación de la ciudad de Machala del año 2010-2011 - Cruz Carmona, Carmen de los Ángeles (2012)
The crisis facing the rehabilitation center of Machala is progressively aggravated, without a relatively clear departure, the indolence of governments to confront the situation reflected in the obsolecta intra-structure in this prison, food is poor, or there are staff Suitable to meet the needs of detainees.